Rhodocetin-αβ-induced neuropilin-1-cMet association triggers restructuring of matrix contacts in endothelial cells - Niland, Stephan; Ditkowski, Bartosz; Parrandier, Désirée; Roth, Lise; Augustin, Hellmut; Eble, Johannes A. (Arteriosclerosis, thrombosis, and vascular biology, 2013)
Objective— - - The snake venom component rhodocetin-αβ (RCαβ) stimulates endothelial cell motility in an α2β1 integrin-independent manner. We aimed to elucidate its cellular and molecular mechanisms. - - Methods and Results— - - We identified neuropilin-1 (Nrp1) as a novel target of RCαβ by protein-chemical methods. RCαβ and vascular endothelial growth factor (VEGF)-A avidly bind to Nrp1. Instead of acting as VEGF receptor 2 coreceptor, Nrp1 associates upon RCαβ treatment with cMet. Furthermore, cell-based ELISAs and kinase inhibitor studies showed that RCαβ induces phosphorylation of tyrosines 1234/1235 and thus activation of cMet. Consequently, paxillin is phosphorylated at Y31, which is redistributed from streak-like focal adhesions to spot-like focal contacts at the cell perimeter, along with α2β1 integrin, thereby regulating cell-matrix interactions. Cortactin is abundant in the cell perimeter, where it is involved in the branching of the cortical actin network of lamellipodia, whereas tensile force-bearing actin stress fibers radiating from focal adhesions disappear together with zyxin, a focal adhesion marker, on RCαβ treatment. - - Conclusion— - - Our data demonstrate that (1) Nrp1 is a novel target for venom components, such as RCαβ; (2) Nrp1 coupled to cMet regulates the type of cell-matrix interactions in a manner involving paxillin phosphorylation; and (3) altered cell-matrix interactions determine endothelial cell migration and cellular force management.